Mavrična knjižnica - Jamnik, Tilka (Knjižnica, 2009)
In the last six decades of development Slovenian youth librarianship has made efforts to establish the youth department as a part of a public library and as a venue for intercultural dialogue. This tendency has been reflected not only in the library collections but also in the programme of library events. It was especially emphasized in the year 2008 which was declared to be the international year of languages and intercultural dialogue. The article describes the impact of intercultural dialogue on library collections. Books for youth acquired by the Center for youth literature and librarianship in the Ljubljana Metropolitan Library are analysed by source and by contents.
Keywords: splošne knjižnice; mladinski oddelki; knjižnične zbirke; mladinska književnost; young adult literature; medkulturno sporazumevanje